Creation of Functional Neo-vagina in Vaginal Atresia - Paudel, Rekha; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Bajracharya, Nishma (Nepal Journal of Obstetrics and Gynaecology, 2018)
Vaginal atresia is one of the common congenital anomalies of the female lower genital tract due to incomplete canalization of Mullerian ducts. It mostly presents as primary amenorrhoea with attacks of severe lower abdominal pain at monthly interval in presence of appropriate Tanner staging secondary sex characteristics. It is diagnosed by clinical presentation, examination and imaging, usually Ultrasound scan and Magnetic Resonance Imaging. There are conservative non-surgical as well as surgical methods to correct it. A 13 years pubertal girl presented at Kathmandu Model Hospital with complaints of cyclic severe lower abdominal pain since one year with presence of appropriate secondary sexual characteristics. Ultrasound showed features suggestive of hematometra. She underwent drainage of hematocolpos with neo-vaginoplasty followed by intravaginal mould placement. She also underwent dilatation of neovagina thrice under IVA to maintain the vaginal length and function. We present here a case of isolated vaginal atresia, who underwent Mc Indoe Vaginoplasty followed by serial dilatation.